The mechanics and deformation of high temperature steel frame rapidly cooled by spray water in fire fighting - Yunchun Xia (Theoretical and Applied Mechanics Letters, 2016)
A finite element is established for analyzing the dynamical mechanics and deformation of steel frame at high temperature when it is rapidly cooled down by spray water in fire fighting. The simulation result shows that remarkable mechanical coupling effects are produced in the process, and the sectional stress in rapid cooling down is found considerably larger than that in heating-up. Meanwhile, the stress and deformation of a beam mainly related to cooling rate and location are much larger than those of a column in rapid cooling. In fire fighting, the structure on the first or second floor was more dangerous than those on other floors in rapid cooling. These results could provide a theoretical reference for the design of steel structure and fire fighting.